Ugunsdzēsēju subkultūra: raksturojums un nozīme Edo perioda pilsētnieku dzīvē - Sviķe, Maija (Latvijas Universitāte, 2009)
Darbā „Ugunsdzēsēju subkultūra: raksturojums un nozīme Edo perioda pilsētnieku dzīvē” ir aprakstīta Edo pilsētnieku ugunsdzēsēju subkultūra, kura ietver sevī pilsētnieku kultūras īpašības, bet kurai piemīt arī savas specifiskas pazīmes. Vispirms tiek apskatīts 18. – 19. gadsimta Edo pilsētnieku dzīvesveids, kas ietekmēja ugunsdzēsēju struktūras izveidi. Pēc tam rakstīts par ugunsdzēsēju vienību izveidošanos un to atšķirībām, kā arī par izmaiņām pilsētas turpmākajā attīstībā, kas ietekmēja pilsētnieku dzīvi. Beidzot uzmanība tiek pievērsta ugunsdzēsēju un pilsētnieku attiecībām, lai noteiktu ugunsdzēsēju subkultūras īpašības.

In the work „The subculture of firefighters: characterization and meaning in the lives of townspeople of the Edo period” there is described the subculture of firefighters of the Edo townsmen, which includes the characteristics of the culture of townsmen but also has its own particular features. First of all, there is examined the lifestyle of the townsmen of Edo in 18th and 19th century, which influenced the foundation of the structure of firefighters. Thereafter, there is written about the establishment and the differences of the firefighter’s units, as well as about the changes in the further development of the city, which had an impact on the lives of the townspeople. Finally the attention is turned to the relations of firefighters and townsmen to define the characteristics of the subculture of firefighters.
The subculture of firefighters: characterization and meaning in the lives of the townspeople of Edo period
Keywords: Āzijas studijas